Familial Pulmonary Capillary Hemangiomatosis Early in Life - Johannes Wirbelauer; Helge Hebestreit; Alexander Marx; Eugene J. Mark; Christian P. Speer (Case Reports in Pulmonology)
Background. Pulmonary capillary hemangiomatosis (PCH) is a rare disease, especially in infancy. Four infants have been reported up to the age of 12 months. So far, no familial patients are observed at this age. Patients. We report three siblings, two female newborns and a foetus of 15-week gestation of unrelated, healthy parents suffering from histologically proven PCH. The first girl presented with increased O2 requirements shortly after birth and patent ductus arteriosus (PDA). She subsequently developed progressive respiratory failure and pulmonary hypertension and died at the age of five months. The second girl presented with clinical signs of bronchial obstruction at the age of three months. The work-up showed a PDA—which was surgically closed—pulmonary hypertension, and bronchial wall instability with stenosis of the left main bronchus. Transient oxygen therapy was required with viral infections. The girl is now six years old and clinically stable without additional O2 requirements. Failure to thrive during infancy and a somewhat delayed development may be the consequence of the disease itself but also could be attributed to repeated episodes of respiratory failure and a long-term systemic steroid therapy. The third pregnancy ended as spontaneous abortion. The foetus showed histological signs of PCH. Conclusion. Despite the differences in clinical course, the trias of PCH, PDA, and pulmonary hypertension in the two life born girls suggests a genetic background.